2011
DOI: 10.1093/jnci/djr156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Inhibitor of the EWS-FLI1 Oncogenic Transcription Factor by High-Throughput Screening

Abstract: Mithramycin inhibits EWS-FLI1 activity and demonstrates ESFT antitumor activity both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
202
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(207 citation statements)
references
References 67 publications
4
202
0
1
Order By: Relevance
“…[32][33][34][35][36][37] Recently, MTM was identified as the lead compound against the Friend leukemia virus integration 1 (EWS-FLI1) transcription factor. 38 EWS-FLI1 is believed to be responsible for malignant transformation and progression of Ewing sarcoma family tumors and was widely regarded as undruggable because it is a transcription factor. 38 A high-throughput screening of over 50,000 compounds identified MTM as the top candidate from the screen and greatly reduced and inhibited tumor volume in Ewing sarcoma family tumors in mouse xenograft models, and it is planned to reinstitute clinical trials for this application of MTM.…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37] Recently, MTM was identified as the lead compound against the Friend leukemia virus integration 1 (EWS-FLI1) transcription factor. 38 EWS-FLI1 is believed to be responsible for malignant transformation and progression of Ewing sarcoma family tumors and was widely regarded as undruggable because it is a transcription factor. 38 A high-throughput screening of over 50,000 compounds identified MTM as the top candidate from the screen and greatly reduced and inhibited tumor volume in Ewing sarcoma family tumors in mouse xenograft models, and it is planned to reinstitute clinical trials for this application of MTM.…”
mentioning
confidence: 99%
“…Cells and Culture Conditions-Growth and propagation conditions and characterization of TC32 cells have been described previously (11). EW8 and 5838 cells were obtained from Dr. Lee Helman of the Pediatric Oncology Branch, NCI, National Institutes of Health, whose laboratory performed authentication of the cell lines by short-tandem repeat genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Activity-A high throughput screen (HTS) developed using the Ewing sarcoma cell line TC32 stably transduced with a luciferase reporter construct that reports on EWS-FLI1 activity was used to screen over 60,000 natural products extracts (11). The top scoring extract in the primary screen was that of the African plant Phyllanthus engleri.…”
Section: High Throughput Screening Identifies Ea As An Inhibitor Of Ementioning
confidence: 99%
“…In addition, this study has shown once more how important it is to identify additional therapeutic options for patients with GIST that make use of these tumors' specifi c molecular makeup aside from KIT/ PDGFRA mutations. Especially targeting the transcriptional machinery-either globally or with the aim of reducing the expression levels of specifi c genes (such as KIT and ETV1 )-has recently emerged as an important new angle for the treatment of GIST and other oncogene-driven malignancies (8)(9)(10). For example, inhibitors of the 26S proteasome, such as bortezomib (Velcade), have been shown to inhibit ongoing gene transcription in GIST, leading to a dramatic loss of KIT protein expression and subsequent apoptosis ( 8 ).…”
Section: ;Rosa26mentioning
confidence: 99%
“…For example, inhibitors of the 26S proteasome, such as bortezomib (Velcade), have been shown to inhibit ongoing gene transcription in GIST, leading to a dramatic loss of KIT protein expression and subsequent apoptosis ( 8 ). The SP1 inhibitor mithramycin A, a "classical" transcriptional inhibitor, has recently gained attention again for being the top hit in a 50,000 compound screen against the EWS-FLI1 fusion oncogene in Ewing family sarcoma ( 9 ). It was also identifi ed in a smaller library screen as being effective for GISTs, with its main mechanism of action lying in the reduction of KIT ( 10 ).…”
Section: ;Rosa26mentioning
confidence: 99%